Mondo Marcos mga panulat sa batas militar at ng Marcos babies - Cimatu, Frank; Tolentino, Rolando B. (Anvil Pub., 2010)
A collection of fiction, essays, and poetry in English by writers who grew up during the martial law period under President Ferdinand Marcos.